c - Dolby, Robyn (Watson, A.C.T. : : Early Childhood Australia, 2011)
Everyday learning about promoting positive behaviour explains how parents form connections with their children by following them and taking an interest in what they are doing and how this helps them lead their child when this is needed. This shows how emotional connection comes from reflecting on rather than reacting to children's behaviour.
Includes bibliographical references (p. 28)
Keywords: Behavior modification -- Study and teaching; Child psychology -- Study and teaching; Australian